2016
DOI: 10.1007/s40243-016-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Pt, Pt–Fe/TiO2 cathode catalysts and its evaluation in microbial fuel cell

Abstract: In this present study TiO 2 supported metal catalysts (Pt/TiO 2 , Pt-Fe/TiO 2 ) were prepared by liquid phase photo deposition method. The prepared catalysts were characterized electrochemically. X-ray Diffractometer (XRD) results showed the presence of metal particle deposition on TiO 2 . HR-SEM and TEM results confirmed the nano size of the metal particles and their uniform dispersion on the surface of TiO 2 . Electrochemical methods such as cyclic Voltammetry, linear sweep Voltammetry were used to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…One such promising MFC is soil (S-MFC) with high potential for real-world applications [ 4 , 5 ]. However, their low energy production rate and performance instability limit their application [ 6 ] in the real world. Therefore, optimization (both architectural and biological) is required to achieve optimal S-MFC system performance for direct practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…One such promising MFC is soil (S-MFC) with high potential for real-world applications [ 4 , 5 ]. However, their low energy production rate and performance instability limit their application [ 6 ] in the real world. Therefore, optimization (both architectural and biological) is required to achieve optimal S-MFC system performance for direct practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Although the CV curve began with the anodic sweep, a small amount of hydrogen atoms was adsorbed at the negative potential and then rapidly desorbed at the positive potential. 72–74 It can be observed that the current for EC hydrogen desorption is the lowest on Pt/P25 under dark conditions. Then, all catalysts were irradiated for 5 min to perform PC hydrogen adsorption and then were analyzed via CV.…”
Section: Resultsmentioning
confidence: 99%
“…Metal oxides such as CeO 2 [6][7][8][9], MnO 2 [10][11][12], TiO 2 [13,14] and ZnO [15] have been used as alternatives for the Pt-based electrocatalyst for the ORR. Metal oxides act as promoters during the ORR due to their facile oxygen release and storage capacity, as well as their well-known corrosion resistance [16,17].…”
Section: Introductionmentioning
confidence: 99%